THE EFFECT OF QUALITY OF SCHOOL LIFE AND RESILIENCE ON ACADEMIC STRESS IN STUDENTS - Muhammad Usman Asy’ari; Baidi Bukhori; Lift Anis Ma’shumah (Jurnal Psikologi Integratif, 2019)
This study aimed to test empirically the effect of quality of school life and resilience on academic stress in university students. The subjects of this study were bachelor degree students of Semarang’s Walisongo Islamic State University, who were in their second to eighth semester. Using technique of Purposive Sampling, the samples of 318 students were gathered. Data were collected using Quality of School Life Scale, Resilience Scale, and Academic Stress Scale. The data obtained were analyzed with multiple regression technique. The result of the analysis showed that quality of school life and resilience has effect on academic stress both partially and simultaneously.  Tujuan dari penelitian ini adalah untuk menguji secara empiris pengaruh quality of school life dan resiliensi terhadap stres akademik pada mahasiswa. Populasi dari penelitian ini adalah mahasiswa S1 UIN Walisongo Semarang semester dua sampai delapan. Pengambilan sampel dilakukan dengan teknik Purposive Sampling. Dengan teknik tersebut diperoleh sampel 318 mahasiswa. Pengumpulan data dilakukan dengan menggunakan skala Quality of School Life, skala Resiliensi, dan skala Stres Akademik. Teknik analisis data yang digunakan adalah regresi ganda. Hasil analisis data menunjukkan bahwa quality of school life dan resiliensi berpengaruh terhadap stres akademik baik secara parsial maupun secara simultan.